Penguatan Pengelolaan Sumber Daya Manusia yang Berlandaskan Kearifan Lokal di Masyarakat Baduy untuk Meningkatkan Usaha Kerajinan Tradisional di Desa Kanekes (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
The Baduy community in Kanekes Village has economic potential based on traditional crafts with high cultural value, such as weaving and woven fabrics. However, the management of craft businesses is still carried out in a simple manner without a structured human resource (HR) management system. Problems faced include the lack of a clear division of tasks, inefficient production processes, and limited marketing strategies. These conditions hamper the optimal development of craft businesses. This community service activity aims to strengthen human resource management based on local wisdom in order to increase the capacity of traditional craft businesses in the Baduy community. The solution offered is training and mentoring on simple business management adapted to traditional values. Activities include socializing the importance of HR management, training on the division of labor within groups, improving production skills, and developing marketing strategies that respect local wisdom. The implementation method uses a participatory approach through the stages of preparation, training, mentoring, evaluation, and program sustainability. The community is actively involved in every stage of the activity to ensure the program's suitability to local socio-cultural conditions. This activity results in increased human resource capacity in craft business management, the establishment of a more organized work system, and an increased economic value of craft products. In addition, this activity is expected to produce a community empowerment model based on local wisdom and scientific publications in community service journals.